Vivenciando a experiência do outro: empatia em Edith Stein - Araújo, Marcelo Cabral de (2020)
The research aims to survey the idea of empathy developed by Edith Stein in her doctoral thesis and from there, with other readings and interpreters, to see how the idea resonates in the philosopher's last book, “Science of the Cross”, where the life and work of Carmelo's father, João da Cruz, is described. Show the continuity between works separated by years, but that allow a dialogue forming what is called praxis, allowing to understand that theory and practice can be dialogued with intellectual maturation through periods. Understanding the other through an idea is a fundamental part of the research, as it is demonstrated here through biographical material the way that a literary record can awaken the knowledge of the other through empathy